2010
DOI: 10.17660/actahortic.2010.877.69
|View full text |Cite
|
Sign up to set email alerts
|

Woolliness Control and Pectin Solubilization of 'Douradão' Peach After Heat Shock Treatment

Abstract: Peach fruit ripens and senesces rapidly at room temperatures. The use of cold storage is limited by chilling injury which results in internal breakdown where internal browning and woolliness are the symptoms, and it is difficult to extend their storage life. In this study, effect of high and moderate temperatures on incidence of woolliness and changes of pectin solubilization of 'Douradão' peach fruit during cold storage were investigated. The treatments were: heating at 50°C during 1 and 2 hours (50°C/1h and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Peach [ Prunus persica (L.) Batsch] fruit has a short postharvest life at room temperature because of its high susceptibility to decay pathogens and rapid deterioration in quality . One of the most important postharvest diseases of peach is brown rot caused by the fungus Monilinia fructicola (G.…”
Section: Introductionmentioning
confidence: 99%
“…Peach [ Prunus persica (L.) Batsch] fruit has a short postharvest life at room temperature because of its high susceptibility to decay pathogens and rapid deterioration in quality . One of the most important postharvest diseases of peach is brown rot caused by the fungus Monilinia fructicola (G.…”
Section: Introductionmentioning
confidence: 99%
“…The lower firmness found in the treated fruit during the simulated marketing period may also be related to the higher juiciness and lack of woolliness in these fruits ( Figure 2A). Other authors observed similar results in peaches and nectarines submitted to pre-storage and concluded that the decline in firmness is related to an increase in juiciness and to a decrease in woolliness (Infante et al, 2009;Sasaki et al, 2010). Murray et al (2007) reported that the combination of pre-storage and controlled atmosphere reduced the fruit firmness to values of approximately 6 N, as well as the woolliness, thus maintaining the fruit quality.…”
Section: Flesh Firmness Total Phenolic Compounds and Antioxidant Camentioning
confidence: 65%
“…The effect of pre-storage combined with LDPE packaging on the cold storage of 'Douradão' peaches was shown to be effective in reducing woolliness when the fruits were cold stored for 30 days at 0ºC followed by 3 days at room temperature. The pre-storage also reduced the woolliness in different varieties of peaches and nectarines when the fruits were exposed to room temperature before the cold storage Sasaki at al., 2010;Neves, Campos, Prill, & Roberto, 2013). Choi and Lee (1997) observed a significant effect on the reduction of woolliness using a passive modified atmosphere in 'Yumyeong' peaches when the fruits were compared with unpackaged ones.…”
Section: Woolliness Index Internal Browning Index Pme and Pg Activitymentioning
confidence: 95%
See 1 more Smart Citation